2017
DOI: 10.1038/s41598-017-16560-6
|View full text |Cite
|
Sign up to set email alerts
|

Insect-based diet, a promising nutritional source, modulates gut microbiota composition and SCFAs production in laying hens

Abstract: Insects could be potential nutritional sources both for humans and animals. Among these, Hermetia illucens, with good amount of chitin and proteins, represents a suitable diet replacement for laying hens. Little is known about insect diet effects on the microbial ecology of the gastrointestinal tract and bacterial metabolites production. In this study we investigated the effect of H. illucens larvae meal administration on cecal microbiota and short chain fatty acids (SCFAs) production in laying hens. 16S rDNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
170
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(187 citation statements)
references
References 58 publications
15
170
2
Order By: Relevance
“…Stimulation of bifidobacteria in the gut of elderly people by prebiotic supplementation was found in clinical trials (Guigoz et al, 2002). High-throughput 16S rRNA gene sequencing revealed that in all groups of rats Firmicutes was a dominant phylum that is in accordance with the data of other authors (Golubeva et al, 2015;Byerley et al, 2017). Significant changes of the gut microbiota in different groups were found at the genus taxonomic level.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Stimulation of bifidobacteria in the gut of elderly people by prebiotic supplementation was found in clinical trials (Guigoz et al, 2002). High-throughput 16S rRNA gene sequencing revealed that in all groups of rats Firmicutes was a dominant phylum that is in accordance with the data of other authors (Golubeva et al, 2015;Byerley et al, 2017). Significant changes of the gut microbiota in different groups were found at the genus taxonomic level.…”
Section: Discussionsupporting
confidence: 77%
“…Butyrate is recognized as an essential host energy source (Donohoe et al, ), which can protect the mucus layer from injury (van der Beek et al, ). Positive contribution of Lactococcus and Vallitalea to the change of microbiota was noticed by other authors in humans and animals (Borrelli et al, ; Savage et al, ; Mao et al, ). We did not find significant change of the microbiota in EC group, except decreased abundance of Bifidobacterium .…”
Section: Discussionsupporting
confidence: 55%
“…Previous studies demonstrated that feed additives (prebiotics and probiotics) modulate the microbial ecology of the poultry GIT, and improve gut functionality and consequentially the health status (Jiang et al 2014;Borrelli et al 2017). In this study, pyrosequencing results indicated that dietary supplementation of chicory forage might have benefited intestinal health by increasing the microbial community diversity in caecum of chickens.…”
Section: Discussionmentioning
confidence: 60%
“…In this study, pyrosequencing results indicated that dietary supplementation of chicory forage might have benefited intestinal health by increasing the microbial community diversity in caecum of chickens. Several studies, in fact, revealed that a rich microbial community is associated with a healthy status as a more diverse microbial community shows stronger homeostasis of the intestinal microbial community and resistance to pathogens (Borrelli et al 2017;Li et al 2017). On the contrary, the stimulation of predominant bacteria might have led to a fall in the microbial diversity in duodenum and ileum of chickens fed chicory forage diets compared to the control.…”
Section: Discussionmentioning
confidence: 99%
“…It should also be noted that Flavonifractor spp. are more commonly reported in 16S rRNA and metagenome profiling studies performed in animal subjects (Oakley et al, 2014, Medvecky et al, 2018, Zhang et al, 2018a, Borrelli et al, 2017, Liu et al, 2017a, Liu et al, 2018.…”
Section: Chapter 5 General Discussionmentioning
confidence: 95%